From 11:00PM PDT on Friday, July 1 until 5:00AM PDT on Saturday, July 2, the Shmoop engineering elves will be making tweaks and improvements to the site. That means Shmoop will be unavailable for use during that time. Thanks for your patience!
We have changed our privacy policy. In addition, we use cookies on our website for various purposes. By continuing on our website, you consent to our use of cookies. You can learn about our practices by reading our privacy policy.
© 2016 Shmoop University, Inc. All rights reserved.


Slope of a Line Between Two Points

The slope of a line between two given points is equal to

where "rise" and "run" mean the same things they did when we first learned about the slopes of lines.

Sample Problem

Consider the line drawn here:

We have

{rise} = ({ending y-value}) – ({starting y-value}) = 8 – 4 = 4


{run} = ({ending x-value}) – ({starting x-value}) = 5 – 3 = 2.

This means the slope of the line is

When we calculate the slope this way, we're assuming that we start at the point (3, 4) and travel to the point (5, 8). If the equation of the line is given by the function f, we think of our starting point as (af(a)) and our ending point as (bf(b)):

However, if we want to be contrary, we can instead start at the point (5, 8) and travel to the point (3, 4):

Now our starting point is (af(a)) = (5, 8) and our ending point is (bf(b)) = (3, 4). We find

{rise} = ({ending y-value}) – ({starting y-value}) = 4 – 8 = -4


{run} = ({ending x-value}) – ({starting x-value}) = 3 – 5 = -2.

This means the slope of the line is

When we switched our starting and ending points in the example we changed the signs of both the rise and the run. These two sign changes canceled each other out; we got the same slope either way. The moral of the story is that when we're asked to find the slope of the line between two points, it doesn't matter which point we think of as the "start."

If we have two numbers a and b and a line f(x), we can say that "run" is the distance from a to b and "rise" is the distance from f(a) to f(b). This produces the formulas

{run} = ba

{rise} = f(b) – f(a).

This will work regardless of which point is to the left.

People who Shmooped this also Shmooped...